The Effect of Group Counselling with Mindfulness-Based Cognitive Therapy to Increase Grit Level: A Study on Vocational High School Students - Rusli, Rusdi; Tanaputra, Jennifer Joi; Safitri, Jehan (Universitas Negeri Padang, 2023)
Students’ indecision regarding their interests and their lack of persistence often lead to their careers being irrelevant to the competencies they possess. Grit, as one of the non-cognitive factors that helps a person stay persistent and focused in achieving goals, is needed to have consistency and the ability to overcome obstacles. Aiming to fill the gap in knowledge about previous studies that looked at this topic, this study’s main goal was to increase the grit levels of grade XII students at vocational schools (SMKs) through group counseling using Mindfulness-based Cognitive Therapy (MBCT). This research looked at how MBCT-based group counseling can help students improve their mindful awareness, cognitive patterns, and ability to stay focused on their goals. This quasi-experimental study, employing one group pretest-posttest design, involved 4 grade XII students of a vocational school in Banjarbaru City who had low grit scores, measured using The Grit Scale. Statistical analysis using the paired sample t-test was applied to identify differences in scores between the two groups. The results of this study found that group counseling based on MBCT was effective in increasing grit levels in SMK students in Banjarbaru by increasing the ability of awareness and focus of students to develop new mindsets that lead to positive changes and more appropriate decision-making. With group counseling, a good psychological state will help improve one's self-quality and performance, thus creating potential vocational school graduates. To achieve these goals, vocational schools should have a program that focuses on developing learners‘ psychological aspects and teachers should be specifically trained to assist learners who have difficulties in their studies.